2015
DOI: 10.1177/0194599815617129
|View full text |Cite
|
Sign up to set email alerts
|

Increased Surgical Site Infection Rates following Clindamycin Use in Head and Neck Free Tissue Transfer

Abstract: For patients with a true penicillin allergy, we recommend broader gram-negative coverage with alternative antibiotics, such as cefuroxime, when undergoing free tissue transfer in the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 30 publications
(68 reference statements)
5
73
1
Order By: Relevance
“…In preparing this review, we found a wound infection rate after clean-contaminated head and neck surgery ranging between 2.5% and 64%, and polymicrobial in origin [6, 16-18, 27, 28, 35, 37-40]. Higher BMI, malnutrition, diabetes, liver disease, anemia, peripheral vascular disease, chronic obstructive pulmonary disease, immunosuppressive medication, and higher ASA score increase the risk of wound infection [10,[18][19][20][21][22][23][24]. Other factors include extensive surgery with flap reconstruction and neck dissection, previous chemotherapy, and a perioperative tracheotomy [7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In preparing this review, we found a wound infection rate after clean-contaminated head and neck surgery ranging between 2.5% and 64%, and polymicrobial in origin [6, 16-18, 27, 28, 35, 37-40]. Higher BMI, malnutrition, diabetes, liver disease, anemia, peripheral vascular disease, chronic obstructive pulmonary disease, immunosuppressive medication, and higher ASA score increase the risk of wound infection [10,[18][19][20][21][22][23][24]. Other factors include extensive surgery with flap reconstruction and neck dissection, previous chemotherapy, and a perioperative tracheotomy [7].…”
Section: Discussionmentioning
confidence: 99%
“…In general, a first-generation cephalosporin like cefazolin is the drug of choice; equally effective are amoxicillin-clavulanate and ampicillin-sulbactam, independent of the need for flap reconstruction [18,24,27]. Other antibiotics, such as benzylpenicillin [24] and clindamycin [5,8,10,19,23,27,38,43], are inferior. Of note, in the USA, ampicillin-sulbactam is available as a single pharmacologic preparation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations